Ghosts, vampires, and werewolves : eerie tales from Transylvania - Spariosu, Mihai; Benedek, Dezso; Kubinyi, Laszlo, 1937- (New York : Orchard Books, 1994)
Includes sixteen tales from Transylvanian folklore, arranged in three sections: Ghosts, vampires, and werewolves; Haunted treasures; and Eerie fairy tales.
Includes bibliographical references (p. 104).
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
6.6
5-8
Keywords: Tales -- Romania -- Transylvania; Folklore -- Romania -- Transylvania; Supernatural -- Folklore; Folklore -- Transylvania (Romania); Supernatural -- Folklore